Brief Overview of Targeted Dumping Rules - Linxuan Liu (Studies in Law and Justice, 2023)
In light of increasing trade friction between China and developed economies, protecting the legitimate rights and interests of domestic enterprises in anti-dumping investigations is of great importance. Targeted dumping, which emerged during the Uruguay Round negotiations in 1994, has become a central issue in anti-dumping investigations. This paper aims to provide a comprehensive definition of targeted dumping while analyzing its historical evolution from the zeroing method to the concept of targeted dumping, alongside assessing the rules and frameworks for its application in the United States, which have reflected its ambiguity and uncertainty. The paper will also analyze the case of United States - Certain Methodologies and Their Application to Anti-Dumping Proceedings Involving China (“DS471”) and discuss the relevant central issues of targeted dumping. What we would conclude is that by analyzing the findings from the Panel and the Appellate Body of the World Trade Organization (“WTO”) regarding this case and other relevant favorable verdicts of illegality or ineffectiveness of methods used to determine target dumping in recent years in-depth, it would be a benefit for Chinese enterprise from the perspective of the response to the determination of anti-dumping measures regarding target dumping.